Introduction to Special Issue 6.1, Censorship and Young Adult Literature - Dani Kachorsky (University of Oklahoma Libraries, 2023)
For this special issue of Study and Scrutiny: Research on Young Adult Literature, we welcome guest editor, Dani Kachorski, who created the call and worked diligently to usher in the scholarship of educators and researchers from all contexts. At Dr. Kachorski's suggestion, we opened up the journal to other scholarly genres and we are delighted to offer them here.